Assessment the suitability of the drinking water distribution network for population changes in the lattakia city using modern software - الزعبي اسامه (Latakia University Journal -Engineering Sciences Series, 2023)
As a result of the high population density and urban expansion saw by the city of Lattakia in the recent period and the power outages for long periods, this led to a decrease in the efficiency of the drinking water network. The research focus on the developments of the drinking water network in the city of Lattakia for the years 2017 and 2022, and its suitability for population growth, highlighting the obstacles affecting the efficiency of the drinking water network, and identifying areas of damage in parts of the network and the most affected neighborhoods. In this research the data obtained from field surveys has been used as well as the archifed data of the Lattakia Water Company, a spatial model was created for Lattakia water network using Geographical information system GIS. After that, the hydraulic model was created using the WATERGEMS. Then the model was exported to the EPANET for hydraulic simulation, and the GIS program was used to classify and display the results of the hydraulic simulation. The results of the analysis of the network for the year 2017 showed that the pressures in most areas of the city ranged between (3-5) bar, while the pressures decreased in the network nodes for the year 2022, as most of the nodes became within the pressure of (1-3) bar, and the water cut-off areas in the city increased. The results of the velocity analysis in the pipes showed that the majority of the pipes have a velocity of less than (0.5) m/s, which is an unachieved velocity, and that was in the years 2017 and 2022.